USING QUIZIZZ IN ONLINE READING ASSESSMENT FOR 2ND GRADE OF PUBLIC HIGH SCHOOL STUDENTS (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
The writer conducts this research to find the benefit of using Quizizz application in online reading assessment for 2nd grade of public high school. How extensive Quizizz application use for online reading assessment by students, teachers and school department. This research is using study case of qualitative research method by observation to collect the data. The writer find that Quizizz has many benefits and extensive to use for online reading assessment. Due to Quizizz have many interesting features that can be used such as: memes, audios, pictures, animation to make the assessment for fun. Quizizz also has leaderboard that can be motivated students to get better score than their friends.  It also can be decreasing studentÃ¢â‚¬â„¢s anxiety when they take the online reading assessment. In other hand, based on this research Quizizz is appropriate application to use in online reading assessment.
Keywords: Quizizz; Reading; Assessment; Online reading assessment